Changes in the lipid contents of freshwater bivalve, Lamellidens marginalis from godavari river during different seasons (M.S) - R, Jadhav M; R, Gulave A; N, Vedpathak A (Journal of Experimental Sciences, 2013)
Changes in the lipid contents different soft body tissues of Lamellidens marginalis (70-77 mm in shell length) were collected from Godavari river at Paithan 49 km away from Aurangabad city. The lipid content maximum found in foot during summer and maximum showed in gonad during monsoon and winter season. The freshwater bivalve shows maximum changes in the lipid contents from gonad, as it undergoes different stages like development, maturation and spawning during different seasons.